EFEKTIVITAS PENGELOLAAN PERPARKIRAN PADA KANTOR PD PARKIR MAKASSAR RAYA DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA MAKASSAR - Muh Wahyudi Mokobombang; Budi setiawati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
This research was conducted with the aim of knowing how the process of managing parking retributions in Makassar City, what are the obstacles experienced in its management so far, the mechanism of collection, deposit until it arrives at the acceptance process into PAD which leads to / is beneficial for the development of Makassar City. The type of research that will be used is descriptive research type, which is a type of research that aims to provide a systematic, factual and accurate description of the data in the field regarding regional retribution which is focused on the management of parking fees in Makassar City. Data collection is done by means of surveys, interviews, observations, questionnaires. Based on the results of the research conducted, it can be seen that the parking retribution management process is managed by the Makassar Raya Parking Area Company, starting from payments made by service users to parking attendants, parking attendants depositing to collecting officers, receiving treasurers and then deposits to the City Government until they can be paid for. referred to as PAD Makassar City from the levy sector, especially parking.